Implementation of Evidence-based Maintenance at the University of Ottawa Heart Institute to Optimize Biomedical Engineering Department Maintenance Strategies - Bruch, Sarah; Zakutney, Timothy J.; Chan, Adrian D.C. (CMBES Proceedings, 2017)
No Abstract